PENGARUH CELEBRITY ENDORSER KOREA SELATAN PADA BRAND EQUITY DENGAN BRAND CREDIBILITY DAN BRAND IMAGE SEBAGAI VARIABEL MEDIASI (Studi Pada Pengguna Produk Whitelab) - Wardhani, Hernita Wisnu; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Celebrities are often used by companies to introduce their products or services. The product or service can be a recent release or an existing one. Whitelab adds to the long list of local brands following the Korean Wave phenomenon by collaborating with Sehun, a member of boy group EXO from South Korea. Credible celebrity endorsers are expected to have an impact on brand equity. The study was conducted on 200 respondents through a quantitative questionnaire with closed questions that had a Likert scale of 1-5. Research analysis was carried out using the Structural Equation Model (SEM) method using AMOS software. The results of the study show that celebrity endorsers do not have a direct effect on brand equity, but through the influence of brand credibility. Celebrity endorsers have a positive and significant effect on brand credibility and brand image. It was found that brand image has no significant effect on brand equity. With this, brand credibility positively influences consumers' ideas as well as helps to increase brand value.